Nonsmooth Dynamic Tracking Control for Nonlinear Systems With Mismatched Disturbances: Algorithm and Practice - Dong, Xin; Zhang, Chuanlin; Yang, Tianxiao; Yang, Jun (IEEE transactions on industrial electronics (1982), 2023)
This article addresses a dynamic tracking control issue for a class of nonlinear systems subject to mismatched disturbances. As an alternative control design algorithm for practitioners, a simple nonsmooth tracking scheme with a self-tuning scaling gain is proposed under a nonrecursive synthesis framework. In reference to the existing related works, a main distinguishable feature is that the scaling gain of the proposed regulation law can be adaptively adjusted subject to different perturbation levels; therefore, the control system is able to achieve an improved transient-time control performance while an accurate tracking objective is guaranteed. In addition, the proposed nonrecursive design philosophy is able to obtain the simplest state-feedback expression of the controller through essentially detaching the stability analysis with controller design procedure, i.e., without going through recursive determination steps of classical virtual controllers. The efficacy of the proposed method is validated by an illustrative numerical example and a real-life application to a dc-dc boost converter system.